DESAIN FORMULASI STRATEGI BISNIS PADA 29 DIMSUM DI SUBANG - Sopiawadi, Mutqi; Wina, Neng; Zahra Kirana, Regina; Paujiah, Wari; Winengsih, Wiwin (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
This research develops a business strategy for 29 Dimsum in Subang Regency through the evaluation of internal and external elements utilizing SWOT analysis and the IFAS-EFAS matrix. Information was gathered via observations and interviews with the owners. Findings reveal that 29 Dimsum's strengths include high-quality raw materials, strategic locations, and diverse products, while opportunities arise from high consumer demand for fast food and digital transaction convenience. Challenges include intense market competition and the lack of an official business license. Strategic recommendations focus on product development, enhanced digital marketing, and strengthening the reseller network. The study concludes that 29 Dimsum has considerable growth potential through strategies emphasizing product innovation, operational efficiency, and improved human resource quality for sustainable success in a competitive market.